PERANAN PENGGUNAAN INFORMASI AKUNTANSI PADA KINERJA UNIT BISNIS DALAM BERBAGAI TINGKATAN KOMPETISI PASAR - LINDA CHRISTIANI SUDARMADJI (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
In the era of globalization demands will be quality products and services are getting older. The representation of and service to consumers with a conventional system will not be able to make a firm stand the competition, therefore the company must think to develop and utilize his strategy. One way to do that is by doing a repair on an ongoing basis. Accounting Systems Management (ASM) is an important source of information to assist managers in controlling its activities as well as reduce uncertainty environment so that the organization can achieve success. So the likelihood of occurrence of small companies that implement a failure for this information. Companies can apply ASM information as the basis for making decisions that will improve the performance of business units in different levels of market competition. The level of competition occurs due to many factors that influence, so the company must act fast in responding to those situations.